Outcomes of the Extended Z-Cut Osteotomy for Correction of Adult Acquired Flatfoot Deformity. (August 2019) - Ebaugh, M. Pierce; Larson, David R.; Reb, Christopher W.; Berlet, Gregory C.
Background: Medial displacement calcaneus tuberosity osteotomy and anterior process lengthening calcaneus osteotomy are traditional single-plane osteotomy techniques used in adult acquired flatfoot deformity reconstruction. More recently, 3-plane step-cut osteotomies were described for each of these and shown to offer improved rotational stability via the horizontal limb. However, a major technical challenge is achieving a sufficiently long horizontal limb to correct deformity through lengthening without losing bony apposition. Combining the anterior process and tuberosity step-cuts using an elongated horizontal limb alleviates this technical challenge, creates a very large surface area for bony healing, and utilizes a single incision. We hypothesized that the Z-cut osteotomy would achieve clinical and radiographic flatfoot deformity correction with a high union rate. Methods: This was an institutional review board-approved retrospective study of 16 patients who underwent Z-cut osteotomy for the treatment of moderate to severe symptomatic adult acquired flatfoot deformity, stage IIA/B. The mean radiographic follow-up was 8.8 months, while the mean clinical follow-up was 2.36 years. Radiographic correction was assessed via weightbearing radiographs taken preoperatively and at a mean of 26 ± 2 weeks postoperatively. Measurements included Meary's angle (talo–first metatarsal angle), talonavicular (TN) joint uncoverage percentage, TN incongruency angle, medial cuneiform to fifth metatarsal height, and calcaneal pitch. Union rates and clinical outcomes via the Foot Function Index (FFI) score were assessed preoperatively and at a mean of 29 months following surgery. Paired t test was used to compare both clinical and radiographic outcomes with statistical significance set at P < .05. Results: Fifteen of 16 patients returned an FFI questionnaire with a mean improvement of 52.1 to 10.3 ( P = .002). The calcaneal pitch improved from 12.7 to 15.2 degrees ( P = .002), the medial cuneiform–fifth metatarsal distance improved from 12.8 to 18.5 mm ( P = .002), the TN coverage angle improved from 21.3 to 9.1 degrees ( P < .001), the TN uncoverage percentage improved from 32.9% to 20.3% ( P < .001), and the TN incongruency angle improved from 41.4 to 19.9 degrees ( P < .001). Deformity correction was well maintained in 13 of 16 patients at final follow-up. The union rate of the osteotomy was 100%. Three patients had symptomatic hardware initially; 1 patient required removal of hardware. One patient developed a superficial infection that cleared. Another patient developed peroneal tendonitis, which resolved with corticosteroid injection. Conclusion: The Z-cut osteotomy is a novel, technically simplified, single-incision, single-osteotomy alternative to the previously described double calcaneus osteotomy techniques for reconstructing flexible moderate to severe adult acquired flatfoot deformity that offers comparable short-term clinical and radiographic outcomes with acceptably low complications. Level of Evidence: Level IV, retrospective case series.